Ionised graphene oxide membranes for seawater desalination - Dahanayaka, Madhavi (2021)
The graphene oxide (GO) membrane has recently emerged as a promising material for nanofiltration. However, its application in seawater desalination is limited because of the comparatively low ion rejection performance. The ionisation of the functional groups such as carboxylic acid results in a negative charge on the GO sheet. In this study, molecular dynamics simulations have been conducted to investigate the seawater desalination performance of a bilayer ionised GO membrane with experimentally reported nanocapillary size (10 Å) via nanofiltration. The results show that the ionised GO membrane is selective for both Na+ and Cl− ions. Furthermore, this research proposes a method that is more energetically favourable than nanofiltration for enhancing solute rejection by the ionised GO membrane by exposing the membrane to an external electric field opposite to the direction of water flow. The water flux shows a nonmonotonic dependence on the electric field intensity, with solute rejection increasing with an increase in field intensity. At a field intensity of E = 0.6 V/Å, a complete rejection of solute can be realized, with a water flux as high as 0.071 kg/cm2/s. The findings from this study will be helpful for promoting GO as a novel material for seawater desalination membranes.